Morphological and molecular studies on two myxosporean infections of cyprinid fishes: Thelohanellus pyriformis from tench and Thelohanellus cf. fuhrmanni from nase - Urvashi Goswami; Gábor Cech; Kálmán Molnár; Subarna Ghosh; Boglárka Sellyei; István Czeglédi; Csaba Székely (International Journal for Parasitology: Parasites and Wildlife, 2022)
During surveys on myxosporean parasites of Lake Balaton and River Danube fishes, two Thelohanellus spp. were found on tench (Tinca tinca) and on common nase (Chondrostoma nasus). They were identified as Thelohanellus pyriformis and Thelohanellus cf. fuhrmanni, respectively. Myxospores of T. pyriformis from tench were collected from arteria branchialis afferens of gill filaments. The mature myxospores of this species were pyriform in shape and 19 ± 0.6l (18–19.5) long, 8.2 ± 0.54 (7.5–9) wide, 7.3 ± 0.25 (7–7.5) thick containing polar tubules with 9–10 turns. The plasmodia of Thelohanellus cf. fuhrmanni were collected from under the skin of snout of the common nase. The myxospores were pyriform, 16.3 ± 0.39l (15.5–16.5) long, 6.5 ± 0.55 (6.3–7) wide, 6.3 ± 0.53 (5.8–7) thick containing polar tubules with 6 turns. Small subunit ribosomal DNA sequences of both Thelohanellus species differed from other known myxozoans. The myxospores morphology, histopathology and ssrDNA sequences supported a diagnosis of T. pyriformis from tench and T. cf. fuhrmanni from common nase.